(untitled) (Sahayaatra सहयात्रा, 2022)
The objective of the study is to assess the relationship between Employee Motivation and Employee Performance (EP). In this study, the researcher adopted a descriptive research design. The primary data was collected from the managerial and operating level employees at the head office of Nepal Electricity Authority (NEA) through a structured questionnaire using Five Point Likert Scale. The study used a quantitative research design and applied stratified and judgmental sampling techniques combinedly. The total number of populations from NEA was 566. The sample size of the study was 181 employees. However, 300 questionnaires were distributed considering the pandemic of COVID-19 and sampling error. Reliability tests were computed in this study. Reliability was ascertained by calculating Cronbach’s Alpha from the pilot study. Data were analyzed based on descriptive and inferential statistics. Means and standard deviation and correlation and regression analysis were used for data analysis. The model summary indicates that the model has not sufficient power to fit the given data set in the multiple linear regression model. ANOVA indicates the statistical and significant prediction of the outcome variable in the regression model. Since the p-value is less than the significance level, there is a statistically significant relationship between motivation and EP. The regression coefficient indicates that there is a positive and moderate relationship between them. It can be concluded that motivation moderately enhances EP. Promotion pays, and recognition is the main motivation factors for employees at NEA. The study will be useful for policymakers such as in governmental, state-owned enterprises, and even the private sector. Further research can be conducted on other public and private sectors. Employee commitment, training, job satisfaction, etc., can be other dimensions to explore the effect of employee motivation.